ACTUAR DEVELOPMENT IN THE ECONOMY OF AGRICULTURE - Z.A. Baymagambetova,; K.N. Tastanbekova,; A.R. Ibrayeva,; M.К. Zhetpisbayeva,; Zh.E. Nurgalieva, (Academic Journal of Physical and Chemical Sciences, 2019)
Analysis of economic efficiency shows that the formation of market relations in the agricultural sector requires a well-considered and balanced approach, justification of diverse forms of ownership and methods of management. Of particular relevance are the problems of management restructuring, since production efficiency and the solution of the problem of sociologizing the economy and raising the living standards of the population depend on it in the first place. From the perspective of the insurance company, in order to choose the level of protection against losses in the agricultural sector, a clear understanding of the nature, specificity, nature, volume and frequency of losses faced by the parties of the insurance process in agricultural insurance is required, which is described in more detail by the authors in this article.